The prognostic value of postoperative radiotherapy in right tumor for lung related death: based on SEER database and real-world data - Mo, You; Chen, Minxin; Wang, Minglei; Wu, Meng; Yu, Jinming (Frontiers in Oncology, 2023)
Background Postoperative radiotherapy (PORT) is a therapeutic strategy for patients with non-small cell lung cancer (NSCLC). Nevertheless, some studies suggesting PORT does not improve overall survival (OS) including Lung ART phase III trial. The role of PORT and high-risk groups need to be confirmed. Methods Patients from the Surveillance, Epidemiology, and End Results program (SEER) from 2004 to 2015 were eligible. Aged ≥18 years with stage IIIA-N2 NSCLC, accepted PORT or not were considered for the study. Cox regression analyses and multivariate competing risk model were performed. Propensity score matching (PSM) was conducted. Data from a single-center study in China were used for validation. Results In all patients with IIIA-N2 NSCLC, death from respiratory illness increased year by year, with right lung-related deaths accounting for the main proportion. In SEER database, PORT was detrimental for OS after PSM (hazard ratio [HR], 1.088; 95% CI, 1.088–1.174; P = 0.031), with a same trend for death from the lungs (HR, 1.13; 95% CI, 1.04–1.22; P = 0.005). Right tumor receiving PORT were prone to death from lung disease(HR, 1.14; 95% CI, 1.02–1.27; P = 0.018). In China single-center cohort, PORT was significantly correlated with deteriorated OS (HR 1.356; 95% CI 1.127–1.632; P <0.01), especially in the right laterality (HR 1.365; 95% CI 1.062–1.755; P = 0.015). Conclusions PORT was a risk factor for stage IIIA-N2 NSCLC patients, particularly with characters of right laterality, male sex, age ≥65 years, and advanced tumor stage. These patients are more likely to death from lung disease after PORT.